ANALISIS DISIPLIN KERJA, AKSEBILITAS DAN PRODUKTIVITAS TERHADAP KINERJA GURU DI SMAN 4 MEDAN - Darmilisani Darmilisani; Nuraini Kemalasari Istiqamah; Riska Fadhillah Hasibuan (LP2M Universitas Bina Bangsa, 2024)
This study aims to analyze the effect of work discipline, accessibility, and productivity on teacher performance at SMAN 4 Medan. The type of research used is quantitative research. The population used was all teachers at SMAN 4 Medan, which was 49 people and made the entire population into a sample, so that the number of research samples amounted to 49 people. Data collection techniques are carried out using questionnaires. The results showed that partially work discipline had a significant positive effect on teacher performance with a correlation of 0.317 and a significance value of 0.000 < 0.05. Partial accessibility did not have a significant positive effect on teacher performance with a correlation of 0.048 and a significance value of 0.371 > 0.05. Partial compensation had a significant positive effect on teacher performance with a correlation of 0.168 and a significance value of 0.000 < 0.05. Work discipline, accessibility, and productivity simultaneously have a significant positive effect on teacher performance with a significance of 0.000 < 0.05. Determination shows a result of 0.623 meaning that work discipline, accessibility and productivity affect teacher performance by 62.3% of all factors that can affect teacher performance at SMAN 4 Medan